"I Trusted Her More Than I Trusted Myself": The impact of academic advising on rural students' sense of belonging in college. Issue 171 (30th April 2021) - Yenney, Caolfionn B.
Abstract: This chapter explores the impact of academic advising on rural students' sense of belonging in college and outlines opportunities to provide further institutional support for rural students.